Предмет: Алгебра,
автор: nikolajfedotov451
упростите выражение
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
Сәттілік
Приложения:
Автор ответа:
0
Ответ:
Объяснение:
в) = (x*(x-y)+y*(x+y)) /(x+y)(x-y) =(x^2-xy+xy+y^2) /(x^2-y^2) =(x^2+y^2) /(x^2-y^2)
г) =(3x+y)/x(x+y) - (x+3y)/y(x+y) = (y*(3x+y)-x*(x+3y)) /xy(x+y) =
(3xy+y^2-x^2-3xy) /xy(x+y) =(y^2-x^2) /xy(x+y) =(y-x)(y+x) /xy(x+y) =(y-x)/xy
rano141219:
Привет
Похожие вопросы
Предмет: Русский язык,
автор: nkul70
Предмет: Русский язык,
автор: Ligidovmartin1111
Предмет: Русский язык,
автор: gopnichok1
Предмет: Математика,
автор: суха2
Предмет: Геометрия,
автор: Надя909